2016
DOI: 10.1007/s10495-016-1220-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium MAV2052 protein induces apoptosis in murine macrophage cells through Toll-like receptor 4

Abstract: Mycobacterium avium and its sonic extracts induce apoptosis in macrophages. However, little is known about the M. avium components regulating macrophage apoptosis. In this study, using multidimensional fractionation, we identified MAV2052 protein, which induced macrophage apoptosis in M. avium culture filtrates. The recombinant MAV2052 induced macrophage apoptosis in a caspase-dependent manner. The loss of mitochondrial transmembrane potential (ΔΨm), mitochondrial translocation of Bax, and release of cytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…This phenotype is coherent with our proteomics data which hitherto revealed that the LysX deficiency in MAH arouses a metabolic alteration which represents an intracellular metabolic status found in MTB, thereby equipping the bacteria for intracellular niches of the host organism [28]. In particular, the gene class of ESX export systems which play a pivotal role in mycobacterial virulence [60] (EccA3, MAV_4606, MAV_0940) and those involved in anti-apoptotic pathways (CysK [61], KatG [62], NuoG [63]) were also differentially regulated in the lysXmut strain.…”
Section: Discussionsupporting
confidence: 90%
“…This phenotype is coherent with our proteomics data which hitherto revealed that the LysX deficiency in MAH arouses a metabolic alteration which represents an intracellular metabolic status found in MTB, thereby equipping the bacteria for intracellular niches of the host organism [28]. In particular, the gene class of ESX export systems which play a pivotal role in mycobacterial virulence [60] (EccA3, MAV_4606, MAV_0940) and those involved in anti-apoptotic pathways (CysK [61], KatG [62], NuoG [63]) were also differentially regulated in the lysXmut strain.…”
Section: Discussionsupporting
confidence: 90%
“…Other reports also showed that ROS are involved in M. avium - and its sonic extracts-induced macrophage apoptosis1321. We also demonstrated that ROS production is required for macrophage apoptosis induced by M. avium MAV205222.…”
Section: Discussionmentioning
confidence: 55%
“…The sonic extracts from M. avium cause apoptosis of monocytes and macrophages21, indicating that MAC also contains a component involved in modulating apoptosis. Recently, we identified M. avium MAV2052 protein, which induced apoptosis in murine macrophages22. However, the MAC components involved in inhibiting or triggering apoptosis are not well-understood.…”
mentioning
confidence: 99%
“…We found homologous genes in all NTM strains, with exception of MAV_4563 (coding for a protein with unknown function), which is absent in the M. smegmatis , and the gene coding for a divalent metal cation transporter (MAV_2120), which was exclusively present in M. avium strains. This “ M. avium -specific” pattern was also found for the gene coding the cysteine synthase A (CysK; MAV_2052), which was recently described as potential mediator of apoptotic cell death through TLR4 dependent ROS production and JNK pathway in murine macrophages [29]. MAV_2054, which is likely involved in inducing macrophage apoptosis by targeting mitochondria, was present in both M. avium strains as well as in M. smegmatis [30].…”
Section: Resultsmentioning
confidence: 74%
“…In order to screen the genomes of the five NTM strains for the presence/absence of known virulence factors, a custom sequence database was created based on a comprehensive list of genes recently gathered by Fedrizzi and colleagues [23], as well as, additional virulence factors retrieved from literature [24,25,26,27,28,29,30,31,32] or from the Virulence Factor Database (VFDB) [33]. A detailed description of the list of searched virulence-associated genes, namely the “locus_tags” in the reference genomes from which individual CDS sequences were extracted, is presented in Table S2.…”
Section: Methodsmentioning
confidence: 99%